The loss of βΙ spectrin alters synaptic size and composition in the ja/ja mouse - Stankewich, Michael C.; Peters, Luanne L.; Morrow, Jon S. (Frontiers in Neuroscience, 2024)
Introduction Deletion or mutation of members of the spectrin gene family contributes to many neurologic and neuropsychiatric disorders. While each spectrinopathy may generate distinct neuropathology, the study of βΙ spectrin’s role (Sptb) in the brain has been hampered by the hematologic consequences of its loss. Methods Jaundiced mice (ja/ja) that lack βΙ spectrin suffer a rapidly fatal hemolytic anemia. We have used exchange transfusion of newborn ja/ja mice to blunt their hemolytic pathology, enabling an examination of βΙ spectrin deficiency in the mature mouse brain by ultrastructural and biochemical analysis. Results βΙ spectrin is widely utilized throughout the brain as the βΙΣ2 isoform; it appears by postnatal day 8, and concentrates in the CA1,3 region of the hippocampus, dentate gyrus, cerebellar granule layer, cortical layer 2, medial habenula, and ventral thalamus. It is present in a subset of dendrites and absent in white matter. Without βΙ spectrin there is a 20% reduction in postsynaptic density size in the granule layer of the cerebellum, a selective loss of ankyrinR in cerebellar granule neurons, and a reduction in the level of the postsynaptic adhesion molecule NCAM. While we find no substitution of another spectrin for βΙ at dendrites or synapses, there is curiously enhanced βΙV spectrin expression in the ja/ja brain. Discussion βΙΣ2 spectrin appears to be essential for refining postsynaptic structures through interactions with ankyrinR and NCAM. We speculate that it may play additional roles yet to be discovered.